Analisis Politik Hukum Terhadap Penegakan Hukum Restoratif Dalam Kitab Undang-Undang Hukum Pidana Baru - Pratama, Agung Putra (Jurnal Ilmiah Advokasi, 2025)
This research aims to analyze the role of legal politics in the establishment of the new Penal Code (KUHP) in Indonesia, which reflects the values of Pancasila and human rights, as well as the application of restorative justice. The research method used is normative legal research with a legislative approach, through document studies and qualitative analysis of relevant legal sources. The findings indicate that although the new KUHP focuses on rehabilitation and justice, challenges in its implementation still exist, particularly regarding the formalistic approach of law enforcement officials. Enhancing the capacity and understanding of law enforcement regarding the new principles in the KUHP is crucial to creating a more responsive, fair, and humane justice system in line with the aspirations for social justice in Indonesia. Keywords: Legal Politics; KUHP; Restorative Justice